Perception Profile of Content Knowledge and Technological Pedagogy of Chemistry Teachers and the Quality of Their Implementation in the Development of RPP and Chemistry Learning - et. al., Ridwan Joharmawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Content knowledge and technological pedagogy (TPACK) can be seen as the skills and abilities of teachers in selecting and using technology effectively. However, information about the Perception Profile of Chemistry Teachers' TPACK and the quality of its implementation in the development of lesson plans and chemistry learning is still limited. On the other hand, today's learners have grown and developed surrounded by technology, making it an integral part of their daily lives. Students are already using smart phones that can be used as a means of communication, making pictures, videos, transferring data by everyday learners, showing the ability to think and process information that is different from the previous generation. In connection with these developments, it is necessary to have teacher competencies that are able to combine material knowledge, pedagogy and technology that interact with each other and intersect to form Technological Pedagogical Content Knowledge (TPACK). In connection with this background, the purpose of this study is to analyze (1) how is the perception profile of the TPACK chemistry teacher at MGMP Malang in terms of length of teaching and certification status, (2) how is the correlation between teachers' perceptions of TPACK and implementation in RPP development, (3) how is the correlation? perceptions of TPACK with the implementation of Chemistry learning in the classroom, (4) what is the cause of the gap between teachers' TPACK perceptions and TPACK implementation in RPP and TPACK implementation in learning. The research design used is descriptive design, because this research requires quantitative and qualitative data, mixed methods are used in this study. The data analysis in this research is descriptive analysis. In this study, data were obtained in the form of chemical teacher TPACK perceptions, TPACK implementation in RPP development, TPACK implementation in chemistry learning, and interviews with teachers and students. The results showed that: (1) The perception profile of chemistry teachers' TPACK is that most of the chemistry teachers (85%) have TPACK perceptions in the medium category, the rest are in the high and low categories. From the results of the Importance-performance Analysis (IPA) analysis, the teacher was able to apply TPACK perceptions to the implementation of RPP making on the PK, PCK, and TK (volunteer) components with high categories, while the TPK component had low applicability and the low category level was the CK component. From the results of the IPA analysis, the applicability of teachers' perceptions of TPACK in classroom learning was the highest in the CK, PK, and PCK components, while the TPACK components had low TCK and TPACK applicability. The gap in the perception of TPACK teachers with implementation in lesson plans and learning is due to (a) an understanding of the concept of learning as just a knowledge transfer process so that teachers emphasize more on conveying chemical concepts (b) teacher learning experiences while taking teacher education have not got the skills to use technology for learning. (c) the process of preparing lesson plans is carried out jointly, with the target of immediate completion of the real lesson plans, the discussion process for compiling lesson plans that challenges students, encourages students to find concepts, and the use of various media and IT-based does not get an adequate portion (d) availability of facilities and regulations which supports the use of technology in schools is not sufficient.